Millimeter wave carrier generation based on a double-Brillouin-frequency spaced fiber laser - Shee, Yugang; Mansoori, M.H; Yaakob, Syamsuri; Man, Abdullah; Abdul Kadir@Jaafar, Muhammad Zamzuri; Adikan, Faisal Rafiq Mahamd; Mahdi, Mohd Adzir (Optical Society of America, 2012)
An all-optical generation of a millimeter wave carrier from a multiwavelength Brillouin-erbium fiber laser is presented. Four-channel output with spacing of about 21.5 GHz is generated from the fiber laser by controlling the gain in the cavity. A dual-wavelength signal with spacing correspondent to six orders of Brillouin frequency shift is obtained by suppressing the two channels at the middle. Heterodyning these signals at the high-speed photodetector produces a millimeter wave carrier at 64.17 GHz. Temperature dependence characteristic of Brillouin frequency shift realize the flexibility of generated millimeter wave frequency to be tuned at 6.6 MHz / °C.